Simulated and experimental study of the chip deformation mechanisms of monocrystalline Cu - Bing Liu; Kai Jiang; Yuxiang Chen; Haijie Yang; Yurong Wang; Keyu Sun; Haiyang Li (Nanotechnology and Precision Engineering)
Monocrystalline Cu exhibits excellent electrical and signal-transmission properties due to its absence of grain boundaries, making it a critical material for the production of micro-machinery and micro-components; however, achieving ultrahigh precision and ultralow damage machining of functional devices using traditional techniques such as grinding and polishing is extremely challenging. Consequently, nanocutting has emerged as an efficient means to fabricate monocrystalline materials with complex surface characteristics and high surface integrity. Nevertheless, the macroscopic cutting theory of metal materials cannot be applied to nanocutting. Accordingly, in this paper, both simulations and experiments were conducted to examine the chip deformation mechanisms of monocrystalline Cu. First, large-scale molecular dynamics (MD) simulations were conducted to gain a comprehensive understanding of the deformation behavior during nanocutting. This included examining the influencing factors and the variation patterns of the chip deformation coefficient, cutting force, and minimum cutting thickness. Subsequently, nanocutting experiments were performed using a specially designed nanocutting platform with high-resolution online observation by scanning electron microscopy. The experimental results served to verify the accuracy and reliability of the MD modeling, as they exhibited excellent consistency with the simulated results. Although this work considered monocrystalline Cu, it is believed that the elucidated chip deformation mechanisms could also be applied to other face-centered-cubic metals. These results are of great value for advancing the understanding of the mechanisms of ultraprecision cutting.